The Implementation of ICT-Based Flipped Classroom for Linear Algebra Course - Himmatul Ulya (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
The flipped classroom learning in Linear Algebra learning could be applied as alternative learning that utilizes technology. Hence students involved in the learning and their learning autonomy would be fostered. This article analyzing the stages of Linear Algebra learning, the implementation of learning, and describing the students' learning outcomes. The subjects were the first semester students in the academic year of 2019/2020, of the Mathematics Education Study Program, Universitas Muria Kudus. The data collection technique consisted of test and non-test. The technique test was used to measure mathematics ability while the non-test technique was applied to measure the students' learning autonomies and learning observation. The applied data analysis consisted of a qualitative description. The findings described the stages of the Linear Algebra course. They consisted of designing the course, developing the content and learning media, uploading the learning material, using ICT for the learning, promoting the assessment, and providing feedback facilitation. The course was begin by providing a problem to be solved in a group. The material was uploaded in the e-learning platform. The students were facilitated to create groups. They were then allowed to find solutions stage via the internet accessed from their handphone/laptop. They were then asked to solve the problems on the given worksheet manually and utilizing the computer program. After discussing, they presented the results. The average of their mathematics ability reached a predicate of B while their learning autonomy was in the excellent criterion. Keywords: Flipped Classroom, Learning Outcomes, Linear Algebra Course